Вибори президента за законодавством України та Російської федерації: порівняльний аналіз - Козоріз, Віра Миколаївна (My University, 2010)
В статье проведен сравнительно-правовой анализ законодательных положений выборов президента в Украине и Российской Федерации. Как законодательство Российской Федерации, так и законодательство Украины большое внимание уделяет выборам президента, так как это один из важнейших институтов современной демократии.

This article deals with the comparative-legal analysis of legislative of presidential elections in Ukraine and Russian Federation. Both the legislation of Russian Federation and the legislation of Ukraine pay much attention to the holding of presidential elections as it is one of the most important institutions of modern democracy. The author reveals the fundamental aspects of this problem, they are legal regulation, the terms of appointment and holding of elections, status of election committee, the role of mass media, status of the candidates and ﬁ nancing of the elections.
Keywords: вибори президента; порівняльно-правовий аналіз; інститут сучасної демократії; проведення виборів; Україна; Російська Федерація; выборы президента; сравнительно-правовой анализ; институт современной демократии; проведение выборов; Украина; Российская Федерация; presidential election; Comparative Legal Analysis; Institute of Modern Democracy; conduct of elections; Ukraine; The Russian Federation